ORGANIZATIONAL BEHAVIOUR, MANAGEMENT THEORY AND ORGANIZATIONAL STRUCTURE: AN OVERVIEW OF THE INTER-RELATIONSHIP - Oluwayemi, Oginni Babalola (Archives of Business Research, 2018)
The paper presents an overview of the organizational behaviour (OB) and its relationship with management theory and organizational structure. It examined the concept of organizational behaviour from a number of perspectives exploring the prevailing definitions and the scope of the discipline. The relationship between OB and management theory was examined and it was noted that OB is an offshoot of management theory, and a macrocosm of the component theories in management theory, where the mainstream management theories have contributions towards the development of OB as a field of study. The exploration of the link between OB and organizational structure revealed that both are interactive. Structure affects OB at all levels and OB determines the choice of structural design. The promotion of work behaviour that enhances productivity and organizational performance constitutes the nexus between organizational behaviour, management theory and organizational structure. The specific areas of management which constitute the subject areas for OB analysis include leadership, power and authority relations, interpersonal communication, conflict and attitude development & perception among others. The paper presented the major contemporary challenges in management theorization which are amenable to OB analysis to include internationalization, workforce diversity, production quality and productivity, employee empowerment, change management and ethical behaviour.